KAJIAN METODE EKSPOSITORI - MODEL PEMBELAJARAN LANGSUNG DAN MODEL PEMBELAJARAN KOOPERATIF - ., Bistari . (Jurnal Pembelajaran Prospektif, 2017)
As a teacher, it is advisable to know the learning component. The goal is that the learning can be more directed and effective. The achievement of learning objectives is more appropriate if the learning component used is appropriate. The learning components as follows: (1) learning theory; (2) learning approach; (3) learning method; (4) learning techniques; (5) tactics learning; (6) learning strategies; and (7) learning model. In this paper the expository method is exposed, direct learning model and cooperative learning model. Expository method is one of the learning methods that teachers often use in the implementation of learning in the classroom. Cooperative learning model is a model of cooperative learning that does not have  a certain type, the characteristic is still common. While the direct learning model presented to emphasize if observed carefully when the teachers taught between direct learning model and expository methods were similar. The difference is in the principle, the method with principle has characteristic, while model with principle has steps of learning.